Pengaruh Fish Bank Bamboo Terhadap Kelimpahan Sumberdaya Ikan di Desa Bomo Kecamatan Blimbingsari Kabupaten Banyuwangi - Herman Puji Effendi; Ernik Yuliana; Nurmala Pangaribuan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The utilization of fish resources which is not environmental friendly can impact aquatic ecosystems damage, mainly fish habitats damage such as coral reefs. Damage coral reefs resulted in decreasing in fish resources, it this case the reefs has a function as a spawning ground, nursery ground, and feeding ground. The decreasing of fish resources can be seen from the decline of fish catched, reduction in the size of fish captured, hard and far away from fishing ground and the scarcity of some species. Many effort can do to return the fish resources on damage aquatic area, one of effort is Fish Bank Bamboo. This Fish Bank Bamboo study expected could be describe about Fish Bank Bamboo development, and to know the direct impact to the fisherman mostly in Bomo, Banyuwangi. Data collecting such as direct observation of Fish Bank Bamboo, interview with the fisherman and collected data of captured fisheries from government official. Fish Bank Bamboo method analysis comprise fish species composition, fishes abundance, diversity index and fish domination index as an indicator of Fish Bank Bamboo success in Bomo aquatic. The observation result inidicated by analyzed the level of success in the fish resources recovery in Bomo, Banyuwangi. Fish Bank Bamboo placement on Bomo aquatic could regenerate fish resources, seen from the success of fish species improvement, increased catch result up to a near distance of fishing ground and eficiency on fishing time. Fish Bank Bamboo could repairing damage aquatic ecosystem, especially in Bomo, Banyuwangi, East Java.